Documentary sources of Philippine history - Zaide, Gregorio F.; Zaide, Sonia M. (Metro Manila National Book Store, 1990)
This twelve-volume documentary source contains 725 historical documents, arranged chronologically (according to dates when events occured or when they were written or published). It includes a brief introduction on the importance of each document to Philippine history. With the publication of these documentary sources, the compiler aims to : a) prove to the intellectuals of the world that the Filipino historian can write a documentary history of his country which can equal or surpass any such work written by foreign scholars; b) improve, correct, upgrade and complete the Blair and Robertson series which contains several defects; c) leave a lasting legacy to the Filipino people who showed the world their magnificent courage and love for freedom and democracy in the unprecedented and peaceful "People power revolution" of Feb. 22-25, 1986.
Keywords: Philippines -- History -- Sources